The Need Analysis of E-Module Development Combined with KingDraw Application on Isomer Material at SMA Al Islam 1 Surakarta - Nisa Nur Hayati; Sentot Budi Rahardjo; Endang Susilowati (Proceeding of the International Conference on Mathematical Sciences, Natural Sciences, and Computing, 2024)
This research was conducted with the aim of analyzing the need for the development of a chemistry e-module combined with the KingDraw application on isomer material at SMA Al Islam 1 Surakarta. This study uses a survey methodology with a qualitative approach. Data were obtained from interviews with chemistry teachers and the results of filling out questionnaires by 84 students. The results of this study indicate that teachers have not developed technology-based teaching materials that can help students in learning chemistry. The teaching materials used are in the form of textbooks containing writings and several two-dimensional images. Thus, it can be said that learning is still conventional and has not followed the development of the digitalization era. This is indicated by the minimal use of technology in learning activities. In learning, teachers only rely on lecture and discussion methods. Therefore, it can be concluded that the development of a chemistry e-module collaborated with the KingDraw application needs to be implemented to motivate students to learn and improve their understanding of chemical concepts independently. This module can also be used anytime and anywhere.